2008
DOI: 10.1095/biolreprod.107.065003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets Enriched in Omega-3 and Omega-6 Polyunsaturated Fatty Acids on Offspring Sex-Ratio and Maternal Behavior in Mice1

Abstract: There have been many trials describing the effects of polyunsaturated fatty acids (PUFA) on fecundity, neonatal development, and maternal behavior in humans, but few controlled studies in rodents. We examined the effects of a maternal diet high in omega 3 (N-3) or omega 6 (N-6) PUFA on NIH Swiss mice. Female mice were ad libitum fed one of three complete and balanced diets (N-3, enriched in menhaden oil; N-6, enriched in corn oil; C, control diet, Purina 5015) from age 4 wk until the end of the study. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 39 publications
0
47
1
Order By: Relevance
“…Then, further investigation on the effect of high-fat diets (which involved discriminating between diets high in the omega 3 and omega 6 components of polyunsaturated fatty acids) found that the sex ratios were reversed (Fountain et al 2008). The mice fed the high-fat diet enriched with omega 6 gave birth to a significantly higher number of female offspring.…”
Section: Problem 3: Seemingly Contradictory Results In Studies Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…Then, further investigation on the effect of high-fat diets (which involved discriminating between diets high in the omega 3 and omega 6 components of polyunsaturated fatty acids) found that the sex ratios were reversed (Fountain et al 2008). The mice fed the high-fat diet enriched with omega 6 gave birth to a significantly higher number of female offspring.…”
Section: Problem 3: Seemingly Contradictory Results In Studies Of Thementioning
confidence: 99%
“…Recognising that testosterone underpins a tendency to dominant behaviour (Bouissou 1978, Christiansen 1998, Grant & France 2001, researchers who favoured the maternal dominance hypothesis sought an association between female testosterone and offspring sex ratio (Grant & Irwin 2005, Grant et al 2008, Helle et al 2008, Shargal et al 2008, while those opting for the good condition hypothesis sought links in the area of diet (Rosenfeld et al 2003, Rosenfeld & Roberts 2004, Cameron et al 2008, Mathews et al 2008, and, more explicitly, unsaturated fats , polyunsaturated fatty acids (Fountain et al 2008, Green et al 2008 and glucose (Kimura et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detecting a sex ratio skew in laboratory models of developmental programming is not straightforward, as many models cull litters to a standardised number of males and females, or a set low number of single sex offspring in order to maximise the plane of nutrition (Khan et al 2003, Chen et al 2008, Tarry-Adkins et al 2010) but do not report pre-culling litter size or gender distributions. Interestingly, however, a few studies have shown that the sex ratio in rodent models can be altered by changing maternal diet (Rosenfeld et al 2003, Rosenfeld & Roberts 2004, and a similar effect has been noted with calorie restriction (Meikle & Drickamer 1986) and increased fats in the maternal diet (Fountain et al 2008). It has been demonstrated that a mouse model utilising a maternal high-fat diet, which may be taken as a proxy for a nutrient-rich plentiful environment, produced litters skewed towards excess males (male fraction 0.67) whereas a low-fat diet in the same animals skewed the ratio towards excess female offspring (male fraction 0.39) (Rosenfeld et al 2003).…”
Section: R4 C E Aiken and S E Ozannementioning
confidence: 90%
“…Two weeks after the Barnes Maze testing, exploratory and anxiety-related behaviors were assessed by using the EPM (66). Additional information is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%